2020
DOI: 10.1101/2020.02.21.960088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteasome-Bound UCH37 Debranches Ubiquitin Chains to Promote Degradation

Abstract: 1The linkage, length, and architecture of ubiquitin (Ub) chains are all important variables 2 in providing tight control over many biological paradigms. There are clear roles for 3 branched architectures in regulating proteasome-mediated degradation, however the 4 proteins that selectively recognize and process these atypical chains are unknown. Here, 5 using synthetic and enzyme-derived ubiquitin chains along with intact mass spectrometry, 6 we report that UCH37/UCHL5, a proteasome-associated deubiquitinas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Proteasome-bound UCH37 is known to exhibit poor DUB activity for isopeptide-linked ubiquitin–protein conjugates, despite showing predominant activity over USP14 against ubiquitin adducts with small leaving groups, such as ubiquitin amidomethylcoumarin (UbAMC) [ 8 , 37 ]. Similar to USP14, UCH37’s DUB activity can be also markedly increased upon binding to RPN13, a ubiquitin receptor on the proteasome [ 14 , 38 ]. Autoinhibition of the apo form of UCH37 is mainly due to (1) the inhibitory position of UCH37-like (ULD, aka RPN13-binding) domain onto the catalytic domain and (2) the active site crossover loop (ASCL), a flexible segment placed just over the catalytic cysteine ( Figure 1 B).…”
Section: A Structural View Of Proteasomal Deubiquitinating Enzymesmentioning
confidence: 99%
See 4 more Smart Citations
“…Proteasome-bound UCH37 is known to exhibit poor DUB activity for isopeptide-linked ubiquitin–protein conjugates, despite showing predominant activity over USP14 against ubiquitin adducts with small leaving groups, such as ubiquitin amidomethylcoumarin (UbAMC) [ 8 , 37 ]. Similar to USP14, UCH37’s DUB activity can be also markedly increased upon binding to RPN13, a ubiquitin receptor on the proteasome [ 14 , 38 ]. Autoinhibition of the apo form of UCH37 is mainly due to (1) the inhibitory position of UCH37-like (ULD, aka RPN13-binding) domain onto the catalytic domain and (2) the active site crossover loop (ASCL), a flexible segment placed just over the catalytic cysteine ( Figure 1 B).…”
Section: A Structural View Of Proteasomal Deubiquitinating Enzymesmentioning
confidence: 99%
“…This seemingly strict requirement for favored UCH37 substrates may explain why UCH37 preferentially cleaves ubiquitin-adducts with small leaving groups over ubiquitin–protein conjugates. Interestingly, a recent study showed that proteasome-associated UCH37 selectively removes K48-branched chains from a complex mixture of ubiquitin conjugates (see also Section 4 and Figure 2 B) [ 14 ]. The topology of the K48-branching point on bifurcate chains might not be impeded by ASCL-imposed steric hindrance, but this model remains to be further explored.…”
Section: A Structural View Of Proteasomal Deubiquitinating Enzymesmentioning
confidence: 99%
See 3 more Smart Citations